Hubungan Grit dengan Organizational Citizenship Behaviour di PT. X Kontraktor Telekomunikasi - Syuhada Putra (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The purpose of this study is to see correlation Grit dengan Organizational Citizenship Behavior di PT. X. Every company need human resource ,in this case is employee whos have ability to carry out responsibility that have been assigned with perseverence,consitent and loyality for whole company life.Those Grit and Orgaizational Citizenship Behavior is the essencial element that a must have by employee because will give better employee perfirmance and better work result, the two variable assumed having psotif correlation. The type or research used in this research is quantitive research. The respondent of this research amounted to 45 people. the method used was the total sampling method by giving a questionnaire in the form of google-from to the whole active employee of PT.X. Result this research is that grit has a positive correlation with OCB based on data taken at PT. X. The higher level of grit possessed by employees, the higher OCB they have, and vice versa, and based on theory and previous research which states that OCB raised by employees can bring benefits to the company. .